Strategic planning as a competitive advantage by using the BSC as a management tool: a case study in application of radioisotope technology at IPEN - VIEIRA, IMARIO (2017)
Strategic planning is one of the most important management tools for organizational decision making. The nuclear area represents a segment of energy production used by many countries in America, Europe and Asia. It is known that in the future nuclear energy can be a major exit to the global energy crisis. The aim of this research was to use the Balanced Scorecard (BSC) as a strategic tool for decision making in a teaching and research institution of the nuclear area - Nuclear and Energy Research Institute (IPEN), located in the city of Sao Paulo, which belongs to the National Nuclear Energy Commission (CNEN) in Brazil. The methodology used in this academic doctoral study was a case study, which considered the period of research from December 2012 to December 2015. The main results expected from this case study are: the improvement of information flow, the view, the increased visibility of an organization providing education and especially research in relation to published works, increased interaction among IPEN and the main global research institutes and centers, increasing academic production of technical articles, indicator improvement, improving the monitoring of management actions, among others. Given the expected results one can conclude that this study will be of great value to the IPEN and also for the Brazilian energy sector, as it will allow and contribute to the dissemination and demystification of nuclear power as an energy source of mankind, its peaceful applications and for the management activity of knowledge and innovation production in the nuclear area of IPEN.